(3QSGdI GdYQHs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi Gdehdi GdEdg GdMGce GdefRg Yf GdYOe hTcQJ YHOg bGFe GdOjf hgGOi GdCee ef GdYHO GdWGFY GdNGVY GdfPjQ s
(3BNQgG (B:s
(3abO deYJ HGdfhQ hGdOdGFd hGdBjGJ hGfMQaJ GdWhGdY hGdfjQGJ hGTJHcJ GdOhGFQ hGdeKdKGJ hGdehdi MSHfG hfYe GdfUjQ GdeYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B59s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3abg GdePGgH GdCNQis